Kak silno hlepeni on - Fišer, Srečko (Hieronymus, 2025)
France Prešeren and Stanko Vraz were contemporaries (the latter, a decade younger, survived the former by only two years); both were romantics, both were ambitious poets. And friends. Prešeren eventually became the Slovene poetic icon par excellence; Vraz joined the Illyrian movement and moved to Zagreb; the Slovenes gave him the label (everlasting, it seems) of renegade while the Croats esteemed him as an excellent poet. The two, however, remained friends; even more, Prešeren, who acted as role model for the younger poet, somehow remained one of his guiding lights of his late utopian literary projects. Vraz’s translations of Prešeren are a specific trace of this relation. In younger days he made translations into Slovene (incomplete and unpublished) of Prešeren’s poems originally written in German; later he translated some of his Slovene texts into his newly acquired (Croat or Illyrian) language. Translations show variations in approach but always a genuine, »subliminal« understanding of Prešeren’s poetry that is not often seen in later versions provided by mature and experienced translators.